Molecular and physiological characterization of indigenous copper-resistant bacteria from Cikapundung River, West Java, Indonesia - WAHYU IRAWATI; NOMMENSEN PANGIHUTAN OMPUSUNGGU; DWI NINGSIH SUSILOWATI; TRIWIBOWO YUWONO (Biodiversitas Journal of Biological Diversity, 2019)
Irawati W, Ompusunggu NP, Susilowati DN, Yuwono T. 2019. Molecular and physiological characterization of indigenous copper-resistant bacteria from Cikapundung River, West Java, Indonesia. Biodiversitas 20: 344-349. The use of indigenous bacteria as bioremediation agents in wastewater treatments plant is a promising solution for tackling the environmental problem. The objectives of this research were to establish the phylogenetic tree and physiological characterization of copper-resistant bacteria isolated from Cikapundung River, West Java, Indonesia. A phylogenetic tree was constructed based on 16S rDNA sequences. Physiological characterization including growth and the potency of bacterial strain for copper accumulation and copper removal was also studied. Five highly copper-resistant bacteria designated as strains CN1, CN2, CN5, CN6, and CN8 have been isolated from Cikapundung river with the MICs (Minimum Inhibitory Concentration) of 5 mM-8mM. Sequence alignment and phylogenetic analysis showed that strains CN1 and CN6 belong to Klebsiella pneumoniae with the similarity of 99%. Meanwhile, strain CN2, CN5, and CN8 belong to Acinetobacter calcoaceticus, Acinetobacter sp. and Escherichia coli with the similarity of 99%, 96%, and 95%, respectively. The highest resistant bacterial isolates were strains CN6 and CN8 with the MICs of 8 mM. The highest accumulation capability was found in strain CN1 with a total of 4.62 mg/g dry weight of cells. Meanwhile, strain CN8 demonstrated the highest copper removal with the value of 48.15%.